The ALLgorithMM: How to define the hemodilution of bone marrow samples in lymphoproliferative diseases - Vigliotta, Ilaria; Armuzzi, Silvia; Barone, Martina; Solli, Vincenza; Pistis, Ignazia; Borsi, Enrica; Taurisano, Barbara; Mazzocchetti, Gaia; Martello, Marina; Poletti, Andrea; Sartor, Chiara; Rizzello, Ilaria; et al. (Frontiers in Oncology, 2022)
Introduction. Minimal residual disease (MRD) is commonly assessed in bone marrow (BM) aspirate. However, sample quality can impair the MRD measurement, leading to underestimated residual cells and to false negative results. To define a reliable and reproducible method for the assessment of BM hemodilution, several flow cytometry (FC) strategies for hemodilution evaluation have been compared. Methods. For each BM sample, cells populations with a well-known distribution in BM and peripheral blood - e.g., mast cells (MC), immature (IG) and mature granulocytes (N) – have been studied by FC and quantified alongside the BM differential count. Results. The frequencies of cells’ populations were correlated to the IG/N ratio, highlighting a mild correlation with MCs and erythroblasts (R=0.25 and R=0.38 respectively, with p-value=0.0006 and 0.0000052), whereas no significant correlation was found with B or T-cells. The mild correlation between IG/N, NRBCs and MCs supported the combined use of these parameters to evaluate BM hemodilution, hence the optimization of the ALLgorithMM. Once validated, the ALLgorithMM was employed to evaluate the dilution status of BM samples in the context of MRD assessment. Overall, we found that 32% of FC and 52% of Next Generation Sequencing (NGS) analyses were MRD negative in samples resulted hemodiluted (HD) or at least mildly hemodiluted (mHD). Conclusions. The high frequency of MRD-negative results in both HD and mHD samples implies the presence of possible false negative MRD measurements, impairing the correct assessment of patients’ response to therapy and highlighs the importance to evaluate BM hemodilution.